A case study of methomyl removal from aqueous solutions by four natural Albanian clays. Issue 3 (9th June 2020) - Xhaxhiu, Kledi; Prifti, Erinda; Zitka, Ondřej
Abstract: This study evaluated the adsorption properties of four Albanian natural clays from the regions of Brari, Currila, Dardha, and Prrenjasi for commercial methomyl from aqueous solutions. Three methomyl concentrations, 0.200, 0.400, and 0.600 mg/ml, were tested at 25°C to study the influence of the insecticide concentration on the adsorption process for each natural clay type. Within 48 hr of contact time, the adsorption pathways of methomyl on the selected clays are well described by a Langmuir‐like adsorption kinetic model and an intraparticle diffusion model. Hydrolysis and desorption inhibit the overall removal process. The increase of methomyl concentration in solution within the first 48 hr leads to linear adsorption increases well described by Langmuir and Freundlich adsorption isotherms and disfavors the desorption step for the Brari, Currila, and Dardha clays. For the methomyl concentration of 0.600 mg/ml, within 24 hr of contact time, the Dardha and Prrenjasi clays reveal 1.471 and 1.956 mg/g methomyl uptake, respectively. The Brari and Currila clays show longer saturation times followed by better methomyl retention. The Dardha and Prrenjasi clays exhibit fast and high adsorption combined with low retention times.